Percepatan Pemulihan Ekonomi Pasca Pandemi Covid-19 Melalui Pengembangan Sektor Industri Halal di Indonesia - Sri Mulyani; Munawar Ismail; Aunur Rofiq (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2022)
The purpose of this study is to examine in more depth the strategy for accelerating economic recovery after the Covid-19 pandemic through the development of the halal industrial sector. This paper uses a qualitative research method with a descriptive approach. Analysis of the data used is content analysis, which is an analysis carried out by conducting an in-depth discussion of the information found. The results of this study accelerate economic recovery after the COVID-19 pandemic through the development of the halal industry, including policies and models for developing human resources, analyzing training needs, developing halal knowledge and skills, developing halal skills training institutions, halal industry training programs, developing halal entrepreneurship. , collaboration, inter-related institutions and continuous evaluation.